2019
DOI: 10.4103/jmu.jmu_125_18
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis and immediate successful management of isolated fetal epignathus

Abstract: Epignathus or enigmatic teratoma is rare congenital tumor, arising from the sphenoid region of the palate or pharynx. A 30-year-old pregnant woman presented at 34 weeks + 2 days’ gestation with a well-defined solid mass measuring 6.47 cm × 5.7 cm arising from the fetal oral cavity. The color flow mapping showed that the mass was well vascularized, especially in its center, and its blood supply was originated from the fetal oral cavity. The newborn has no chromosomal abnormalities or other associated anomalies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
2
5
0
5
Order By: Relevance
“…The presence of the larger tumor was found during the ultrasound exam in the 34th week of pregnancy, similar to other reports 9,10,12,16,19 in which the diagnosis also occurred in the third trimester. Other studies 7,8,20,23 reported the presence of teratoma in the second trimester of pregnancy, and in some 2,14,15 , only after birth.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The presence of the larger tumor was found during the ultrasound exam in the 34th week of pregnancy, similar to other reports 9,10,12,16,19 in which the diagnosis also occurred in the third trimester. Other studies 7,8,20,23 reported the presence of teratoma in the second trimester of pregnancy, and in some 2,14,15 , only after birth.…”
Section: Discussionsupporting
confidence: 90%
“…In this case, the removal of the teratoma was performed early, o the 17th day of life, requiring removal of the residual teratoma two weeks later. The tumor described in this case was classified anatomically and pathologically as mature, as well as the tumors reported by most authors 2,4,6,9,11,12,14,16,19,21,22 . However, even though it is an uncommon occurrence, Kumar et al 7 and Chung et al 8 reported cases of immature teratoma.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…La vía más frecuente del parto fue la cesárea, con protocolo EXIT en un 65,4 % de los casos (n = 36) (9)(10)(11)17,26,27,(29)(30)(31)(33)(34)(35)38,(41)(42)(43)(44)(45)(46)(47)(48)(50)(51)(52)(54)(55)(56)(57)(58)(59)62,63,65); el parto vaginal se presentó en el 20 % de los casos (n = 11) (6,8,12,21,23,25,32,37 ,39,40,49), y se realizó la interrupción voluntaria de la gestación en el 18,1 % de los casos (n = 10) (18,20 ,22,24,28,36,53,60,61,64). Al nacimiento, el género femenino fue el más frecuente, con un 50,9 % (n = 28) (9,10,18,19,21,22,24,26,27,32,34,36,…”
Section: Resultsunclassified